Gut microbiota dysbiosis in polycystic ovary syndrome: Mechanisms of progression and clinical applications - Sun, Yan; Gao, Shouyang; Ye, Cong; Zhao, Weiliang (Frontiers in Cellular and Infection Microbiology, 2023)
Polycystic ovary syndrome (PCOS) is the most common endocrine diseases in women of childbearing age that leads to menstrual disorders and infertility. The pathogenesis of PCOS is complex and has not yet been fully clarified. Gut microbiota is associated with disorders of lipid, glucose, and steroid hormone metabolish. A large body of studies demonstrated that gut microbiota could regulate the synthesis and secretion of insulin, and affect androgen metabolism and follicle development, providing us a novel idea for unravelling the pathogenesis of PCOS. The relationship between gut microbiota and the pathogenesis of PCOS is particularly important. This study reviewed recent research advances in the roles of gut microbiota in the occurrence and development of PCOS. It is expected to provide a new direction for the treatment of PCOS based on gut microbiota.